PEMBINGKAIAN BUDAYA JAWA DAN BELANDA DI DALAM NOVEL BUMI MANUSIA - Denasya Nasution; Said Fadhlain; Reni Juliani (Universitas Teuku Umar, 2019)
The novel Bumi Manusia is a controversial novel that contains Indigenous life in the Dutch colonial period. Pram depicts the cultural differences between Indigenous and Dutch with a very contrast in all aspects in more detail and depth. The purpose of this research is to expose the cultural differences which are framed in the novel Bumi Manusia. This research is also intended to expose the differences between Javanese and Dutch cultures which not only distinguish culture based on appearance and language. This research is a qualitative descriptive study with secondary data which are obtained from the library research, in the form of literature which are related to this research. The results of this study are: 1) Culture can affect one's personality and mindset. 2) The author describes broader cultural differences and is able to criticize the social gap or strata which are formed from the different cultures at the same time. Keywords :Framing Analysis, Media Studies, Bumi Manusia